Blockade of IL-6 inhibits tumor immune evasion and improves anti–PD-1 immunotherapy. (October 2022) - Li, Wenyi; Wu, Zhaokun; Meng, Weidong; Zhang, Chaoting; Cheng, Mingzhen; Chen, Yuehong; Zou, Yini; Li, Kejun; Lin, Simin; Xiong, Wenjun; Wang, Ying; Lin, Yixiong; et al.
Highlights: IL-6 -/- mice are less susceptible to develop tumors, compared to WT mice. Infiltrated CD8 + T cells are found to exhibit high expression in tumor of IL-6 -/- mice. IL-6 acts as a negative regulator in IFNγ-STAT1-MHC-I signaling. Blockade of IL-6 also increased CD8 + T cells in the CT26 subcutaneous tumors and sensitize animals to anti-PD-1 therapy. Abstract: Long-standing inflammatory bowel disease predisposes to the development of colorectal cancer (CRC). Interleukin (IL) -6, a pivotal link between chronic inflammation and tumor progression, has recently been recognized as a potential therapeutic target. The effect of IL-6 on proliferation and metastasis of CRC by activating the STAT3 pathway has been widely demonstrated in recent years, but few on mediating tumor immune evasion. In this study, we found that IL-6 was remarkably overexpressed in CRC and its elevation was associated with a poor prognosis. We studied CRC tumorigenesis in vivo by inoculating MC38 tumors and induced-CRC model via AOM/DSS (azoxymethane/dextran sulfate sodium) in IL-6 deficient (IL-6 -/- ) and wild-type (WT) mice and found that IL-6 -/- mice were less susceptible to develop tumors, compared to WT mice. We detected CD8 + T cells via immunofluorescence and found they exhibit high expression in tumor of IL-6 -/- mice. High level of IL-6 was found in colitis model, with down-regulation of MHC-I molecules. In in vitro experiments, we found that IL-6 may act as a negative regulator in IFNγ-STAT1-MHC-I signaling. In addition, vivo trials also confirmed that MHC-I mRNA level was negatively related to the existence of IL-6. Furthermore, the blockade of IL-6 also activated CD8 + T -cell accumulation and led to the high PD-L1 expression in CRC, which can sensitize animals to anti-PD-1 therapy. Our study provides a research basis for the significant role of IL-6 in tumor evasion and highlights a novel target to improve the efficacy of immunotherapy.